Украинская социология: общественно-исторический и идеологический контексты развития - Степаненко, В.; Рыбщун, А. (Iнститут соціології НАН України, 2009)
In the paper, the peculiarities of the development of Ukrainian sociology in the context of social, historical, ideological and political transformation of Ukrainian society from the end of 19th century up to the current period are studied. At the base of historical-sociological studies and the archive materials, firstly involved in scientific usage, the authors characterize the historical stages and social logics in the development of Ukrainian sociology in the framework of Ukrainian humanities. There are distinguished proto-sociological, academic, the early Soviet, the Soviet and the current periods in the development of Ukrainian sociology, the historical specificity and social-political logics of appearance in functioning of sociological sciences are characterized. The authors conclude that the self-reflexivity of sociology in its historical context is an actual prerequisite for identification of problems and perspectives of the development of Ukrainian sociology as the sphere of science and social expertise, forming its educational tradition, values and standards of sociological community. At the same time, the contextual research of the history of sociological thought turns out to be the historical-sociological study of socio-structural, political, economical, and cultural factors that have conditioned the corresponding sociological orientations and approaches.